IL‐7 derived from lymph node fibroblastic reticular cells is dispensable for naive T cell homeostasis but crucial for central memory T cell survival. Issue 6 (16th March 2020) - Knop, Laura; Deiser, Katrin; Bank, Ute; Witte, Amelie; Mohr, Juliane; Philipsen, Lars; Fehling, Hans J.; Müller, Andreas J.; Kalinke, Ulrich; Schüler, Thomas
Abstract: The survival of peripheral T cells is dependent on their access to peripheral LNs (pLNs) and stimulation by IL‐7. In pLNs fibroblastic reticular cells (FRCs) and lymphatic endothelial cells (LECs) produce IL‐7 suggesting their contribution to the IL‐7‐dependent survival of T cells. However, IL‐7 production is detectable in multiple organs and is not restricted to pLNs. This raises the question whether pLN‐derived IL‐7 is required for the maintenance of peripheral T cell homeostasis. Here, we show that numbers of naive T cells (TN ) remain unaffected in pLNs and spleen of mice lacking Il7 gene activity in pLN FRCs, LECs, or both. In contrast, frequencies of central memory T cells (TCM ) are reduced in FRC‐specific IL‐7 KO mice. Thus, steady state IL‐7 production by pLN FRCs is critical for the maintenance of TCM, but not TN, indicating that both T cell subsets colonize different ecological niches in vivo. Abstract : In peripheral LNs (pLNs) fibroblastic reticular cells (FRCs) are a major source of IL‐7, which is crucial for the maintenance of peripheral T cell homeostasis. Using FRC‐specific IL‐7 KO mice (FRC ΔIL‐7 ), we demonstrate differential IL‐7 requirements for naive (TN ) and central memory T cells (TCM ).